Evaluasi RME Dengan Model Pieces di Rumah Sakit : Study Literature Review - Nannyk Widyaningrum; Anggie Annisa Permatasari; Sheva Arlinda; Siti Marpuah (Inovasi Kesehatan Global, 2024)
Electronic Medical Records (RME) is an information system used to manage patient medical data electronically, which aims to improve the efficiency and quality of health services in hospitals. This study aims to evaluate the performance and effectiveness of RME in hospitals using the PIECES model. The main focus of the research is on the dimensions of Performance, Information, Economics, Efficiency, and Control to identify the strengths and weaknesses of RME and provide recommendations for improvement. This research uses the Study Literature Review (SLR) method which involves collecting and critically analyzing relevant literature from scientific journals, articles and books. The collected data is evaluated based on the dimensions of the PIECES model to provide a comprehensive picture of RME implementation. The research results show that RME can improve data access speed, system response time, and accuracy of medical information, which supports better clinical decision making. Economically, RME helps reduce operational costs and improve work efficiency. However, challenges such as network reliability, data security, and interoperability still need to be overcome to achieve the full benefits of RME. Dimension Control highlights the importance of strict security policies and user training to ensure safe and effective use.